Indoor hydroponic vegetable gardening to improve mental health and quality of life in cancer patients: a pilot study - Roh, Taehyun; Verzwyvelt, Laura Ashley; Aggarwal, Anisha; Satkunasivam, Raj; Hasan, Nishat Tasnim; Trisha, Nusrat Fahmida; Hall, Charles (Frontiers in Public Health, 2025)
BackgroundCancer patients experience significant psychological and physiological challenges, affecting their treatment outcomes and overall wellbeing. Traditional gardening benefits mental health and quality of life but is often impractical, requiring alternatives. This pilot study evaluated the impact of indoor hydroponic gardening on cancer patients’ mental health and quality of life.MethodsA case-crossover pilot study included 36 adult cancer patients from the Houston Methodist Cancer Center, with participants serving as their own control through repeated measurements. Participants received AeroGarden hydroponic systems and engaged in an 8-week gardening intervention. Mental wellbeing, mental distress, quality of life, fruit and vegetable consumption, and pain management were assessed at baseline, 4 weeks, and 8 weeks using validated scales. Data were analyzed using Generalized Estimating Equations (GEE) to account for within-subject correlations over time.ResultsThe study included 36 cancer patients with a mean age of 57.5 years. Significant improvements were observed in mental wellbeing scores (p-trend = 0.042), depression subscale scores (p-trend = 0.003), and global quality of life (p-trend < 0.001) over the 8 weeks. Emotional and social functioning scores also improved significantly (p-trend = 0.001 and p-trend = 0.010, respectively), along with increased fruit and vegetable intake (p-trend = 0.028). While overall pain management scores showed a decreasing trend, these changes were not statistically significant.ConclusionThis study demonstrates that indoor hydroponic vegetable gardening can significantly improve mental health and quality of life in cancer patients, suggesting it as an alternative to traditional gardening. Future studies with larger sample sizes and longer follow-up periods are needed to confirm these findings and explore long-term benefits.